2016
DOI: 10.1177/2158244016668853
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Turkish Pre-Service Teachers’ Knowledge of Autism Spectrum Disorder

Abstract: The purpose of the present study was to investigate knowledge of autism among teacher candidates who are likely to have the initial contact with children with autism within public school system in Turkey. Five hundred and four senior pre-service teachers who were enrolled in four different teacher education programs participated in the study. Data were collected using a survey package at the end of spring semester during the last year of college. Results indicated that pre-service teachers across programs had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 35 publications
2
24
0
3
Order By: Relevance
“…Furthermore, teachers expressed neutral attitudes towards the inclusion of students with autism in general education classrooms (Engstrand & Roll-Pettersson, 2012;Srivastava et al, 2017a), whereas special education teachers, who taught students with autism, had low to moderate levels of knowledge regarding autism, as well as low to moderately effective teaching practices for their students (Hendricks, 2011). Finally, in-service, preservice, and future teachers had no (or limited) knowledge as well as basic misconceptions about autism and the needs of students with autism in inclusive education classes (Ayub et al, 2017;Barned et al, 2011;Finch et al, 2013;Johnson et al, 2012;Rakap et al, 2016;Yasar & Cronin, 2014;Young et al, 2017).…”
Section: Discussion -Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, teachers expressed neutral attitudes towards the inclusion of students with autism in general education classrooms (Engstrand & Roll-Pettersson, 2012;Srivastava et al, 2017a), whereas special education teachers, who taught students with autism, had low to moderate levels of knowledge regarding autism, as well as low to moderately effective teaching practices for their students (Hendricks, 2011). Finally, in-service, preservice, and future teachers had no (or limited) knowledge as well as basic misconceptions about autism and the needs of students with autism in inclusive education classes (Ayub et al, 2017;Barned et al, 2011;Finch et al, 2013;Johnson et al, 2012;Rakap et al, 2016;Yasar & Cronin, 2014;Young et al, 2017).…”
Section: Discussion -Conclusionmentioning
confidence: 99%
“…The results of their research indicate that both groups are receptive to students with autism, but special education teachers have more positive perceptions of students with ASD. Rakap, Balikci, Parlak-Rakap, and Kalkan (2016) investigated the knowledge of 504 senior pre-service teachers who were enrolled in four different teacher education programmes. The findings of their survey indicated that pre-service teachers across programmes had limited knowledge of autism and its characteristics.…”
Section: Turkeymentioning
confidence: 99%
“…Stone (1987) who investigated autism knowledge of pediatricians, clinical psychologists, speech/language pathologists, school psychologists, and other specialists in the field conducted one of the first studies and reported that there were misconceptions in all professional groups; however, the specialists had the most current knowledge. Since the Stone (1987) study, surveys have included knowledge, perceptions, and understanding of other healthcare professionals (Hartley-McAndrew, Doody, & Mertz, 2014;Heidgerken, Geffken, Modi, & Frakey, 2005;Imran et al, 2011;Ozcelik et al, 2015), speech language pathologists (Cascella & Colella, 2004;Schwartz & Drager, 2008), medical students (Shah, 2001), pharmacists (Khanna & Jariwala, 2012), occupational therapists (James, Pizur-Barnekow, & Schefkind, 2014), residents of a college campus (Tipton & Blacher, 2014), pre-service teachers (Hart & More, 2013;Park, Chitiyo, & Choi, 2010;Rakap et al, 2016;Yasar & Kronin, 2014), and educators (Al-Sharbati et al, 2015, Arif et al, 2013Helps, Newsom-Davis, & Callias, 1999;Mavropoulou & Padeliadu, 2000;Syriopoulou-Delli, Cassimos, Tripsianis, & Polychronopoulou, 2012;Yumak & Akgul, 2010). These studies reported mixed findings with respect to professionals' knowledge, perceptions, and understanding of autism.…”
Section: Introductionmentioning
confidence: 99%
“…İlki, bulgular okul öncesi kaynaştırmanın kalitesi ile ilgili daha önce yapılan çalışmalarla (Bakkaloğlu vd., 2017;Yılmaz, 2014) tutarlıdır ve okul öncesi sınıfların mevcut kalitesinin yetersiz olduğu dikkati çekmektedir. Bu durum okul öncesi öğretmenlerinin a) kaynaştırma ve/veya özel gereksinimli çocuklar hakkındaki bilgilerinin sınırlı olması (Altun ve Gülben, 2009;Sucuoğlu, Bakkaloğlu, Demir, Akalın ve Karasu-İşcen, 2014;Varlıer ve Vuran, 2006), b) öğretimi bireyselleştirme ve etkinlikleri uyarlama konularındaki yeterliklerinin sınırlı olması (Özen, Ergenekon, Kürkçüoğlu ve Genç, 2013;Tufan ve Yıldırım, 2013) ve c) özel gereksinimli çocuklarla çalışma konusunda bilgiye ihtiyaçlarının olması Er-Sabuncuoğlu, 2016;Rakap, Balikci, Parlak-Rakap ve Kalkan, 2016) ile açıklanabilir. Öğretmenlerin konuya ilişkin bilgi, beceri ve deneyimlerindeki sınırlılıkları nedeniyle, okul öncesi kaynaştırma sınıflarının kalitesi ile ilgili bu bulguların şaşırtıcı olmadığı söylenebilir.…”
Section: Discussionunclassified